Peran Pendidikan Islam dalam Pembentukan Karakter Religius Peserta Didik melalui Pendidikan Islam Berbasis Kisah-Kisah dalam Al-Quran di Era Disrupsi - Husin, Amir; Asmarika, Asmarika; Fitri, Yona; Syukri, Syukri; Siregar, Isropil (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
Islamic education plays a particularly important role in shaping the character of the nation's children, especially religious character, honest, likes to read, responsible, independent, respects achievement, social care, hard work and others. All of these characters cannot be separated from the orientation of Islamic education. Because Islam always prioritizes safety education in the world and the hereafter. In this study, the method used is a qualitative method with a qualitative-phenomenological approach. The subjects of this study were school principals, teachers, and students at SDIT Imam Asy-Syafii Pekanbaru. The findings in the field related to the role of Islamic Education in the formation of the religious character of students through Islamic education based on stories in the Koran, there are two findings, (1) through intra-curricular education, namely when the teaching and learning process takes place in the classroom. (2) through extracurricular education which is conducted half an hour before the teaching and learning process is carried out.